2016
DOI: 10.1111/add.13398
|View full text |Cite
|
Sign up to set email alerts
|

The indirect effects of childhood attention deficit hyperactivity disorder on alcohol problems in adulthood through unique facets of impulsivity

Abstract: Background and aims-Research has not studied unique impulsivity dimensions as prospective links between childhood attention deficit hyperactivity disorder (ADHD) and alcohol problems. We examined the association between childhood ADHD, 5 facets of impulsivity and alcohol problems in adulthood, and the indirect effects of childhood ADHD-to-impulsivity-toalcohol problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 33 publications
2
52
1
1
Order By: Relevance
“…Elementary and high schools are closer to the families, so they may be in a strategic position to identify children and youngsters that need follow-up, contribute to the development of non-stigmatizing actions, and articulating with the community and health services to promote mental health and well-being to the young people. (22) School dropout favored the child or adolescent to intensify their time on the streets, thus justifying the beginning of drug use. In this initial period, the family recognized the drug use as a consequence of the environment frequented by the youngster.…”
Section: Discussionmentioning
confidence: 99%
“…Elementary and high schools are closer to the families, so they may be in a strategic position to identify children and youngsters that need follow-up, contribute to the development of non-stigmatizing actions, and articulating with the community and health services to promote mental health and well-being to the young people. (22) School dropout favored the child or adolescent to intensify their time on the streets, thus justifying the beginning of drug use. In this initial period, the family recognized the drug use as a consequence of the environment frequented by the youngster.…”
Section: Discussionmentioning
confidence: 99%
“…As such, what Cyders and Smith (2008) have termed positive and negative urgencies, result in decisions that are poorly conceived and impulsively enacted during periods of heightened mood. Recent work from our group (Pedersen et al, 2016) has shown that both negative and positive urgency mediate the association between ADHD and adult alcohol problems in a longitudinal study of individuals diagnosed with ADHD in childhood. Laboratory-based research examining the relation between emotion and decision-making has shown that elicited discrete emotions (short lived/intensely experienced phenomena) influence decision-making and disrupt preexisting cognitive processes (for review see, Angie, Connelly, Waples, & Kligyte, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…ADHD affects about 7% of children (Thomas et al., ), and symptoms persist into adulthood for approximately 60% of these children (Sibley et al., ). Childhood ADHD is associated with more alcohol problems (e.g., Pedersen et al., ) and higher rates of alcohol use disorder (AUD) in adulthood (Groenman et al., ; Lee et al., ). Multiple explanations for these associations have been posited (Molina and Pelham, ), including the following: elevated trait impulsivity (Pedersen et al., ); the existence of a single externalizing spectrum comprising ADHD, conduct disorder, antisocial personality, and AUD comorbidities (Beauchaine et al., ; Serra‐Pinheiro et al., ); and shared genetic liability (Derks et al., ; Knopik et al., ).…”
Section: Adhd and Alcohol Use Problemsmentioning
confidence: 99%
“…Childhood ADHD is associated with more alcohol problems (e.g., Pedersen et al., ) and higher rates of alcohol use disorder (AUD) in adulthood (Groenman et al., ; Lee et al., ). Multiple explanations for these associations have been posited (Molina and Pelham, ), including the following: elevated trait impulsivity (Pedersen et al., ); the existence of a single externalizing spectrum comprising ADHD, conduct disorder, antisocial personality, and AUD comorbidities (Beauchaine et al., ; Serra‐Pinheiro et al., ); and shared genetic liability (Derks et al., ; Knopik et al., ). Although these broad, genetically driven factors contribute significant risk for substance use, that risk likely manifests day to day through micro‐level processes such as momentary, contextual drinking characteristics—in other words how, where, when, and with whom individuals drink.…”
Section: Adhd and Alcohol Use Problemsmentioning
confidence: 99%